Investigating The kreditkerenbanget.com Website as Credit Simulation Web Platform Based on Customer’s perception - Ketut Nila Arta; Wayan Andre Pratama; I Made Agus Oka Gunawan; Gede Indrawan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Current advances in information technology help make it easier to obtain information regarding motorbike credit simulations, one of which is by accessing the website from KKB BCA. This research is qualitative research using observation methods and literature studies in observations related to business processes on this website. Observation involves understanding how the website collects and processes the necessary data from users, including information about vehicle price, down payment amount, interest rate, and credit tenor to credit simulation calculations of estimated monthly payments, describing payment schedules, and providing cost summaries. The website interface is quite easy to understand so users can create simulations without needing a guide. The use of the website can run well as expected so that it can help make it easier for users or consumers to determine credit planning for motor vehicles through the credit simulation on this website.